PENGARUH PERENDAMAN DAGING SAPI (Topside) MENGGUNAKAN SERBUK JAHE TERHADAP KUALITAS FISIK DAGING SAPI - Nugroho, Dimas Fajar; Wianto, Ardian Ozzy; Pramono, Ahmad (Universitas Veteran Bangun Nusantara, 2023)
The research to determine the effect of ginger powder on color values, pH values, and cooking losses in beef. The research material was beef topside, ginger powder and distilled water which consisted of 4 treatments with 4 replications. The first treatment (T0) 0% (control) without giving powder, (T1) 10% ginger powder immersion, (T2) 20% ginger powder immersion, and (T3) 30% ginger powder immersion, each treatment was soaked for 30 minutes. The variables observed were the color test, pH test, and cooking losses. The data obtained were analyzed statistically using a completely randomized design in one direction, the differences between treatments were calculated using Duncan's Multiple Area Test, the percentage of distransformation data used Arcus sinus. Based on the SPSS analysis, it showed that the effect of soaking the topside of the beef using ginger powder with different concentrations showed highly significant different results on the color test (P<0.01) and pH value (P<0.01). However, the results showed no significant difference in the Cooking Shrinkage test (P> 0.05). Color Value: T0 = 2.5; T1 = 5.25; T2 = 7.5; T3 = 8; pH value: T0 = 6.93; T1 = 6.64; T2 = 6.55; T3 = 6.44; Cooking Losses (%): T0 = 41.00; T1 = 42.13; T2 = 41.66; T3 = 43.05. Based on the results of the study it was concluded that the addition of ginger powder with a concentration of 30% had no effect on the cooking loss of meat. However, it has a very real effect on the color and pH of the meat.